«We only have rights over operators». La riappropriazione del “regime di sospetto” da parte dei richiedenti asilo in un centro di prima accoglienza - Castellano, Viola (Antropologia Pubblica, 2017)
The presence and the perception of case workers is a fundamental element in crafting the attitudes and expectations of asylum seekers. Indeed, reception and welcoming centers are the main channels through which asylum seekers come to know the cultural context and the general perception of their presence in the hosting society. Social workers are often the lens asylum seekers use in order to read and orient themselves within the host system. They are also professional figures producing the bureaucratic identity of asylum seekers as subjects of human and civil rights. At the same time, social workers are the “eye” of the state in surveilling the conduct of asylum seekers and are expected to denounce nonconformity. As a consequence of such multiple roles, in a bureaucratic immigration system characterized by opacity and a high degree of conflict, the encounter between asylum seekers and social workers becomes a crucial site heavily invested with disparate meanings and desires. In particular I would like to stress the point on how regimes of suspects and the uncertainty paradigm become fundamental element in crafting asylum seekers subjectivities. On the other hand, I highlight how they are not passive, grateful and unaware suffering subjects, but they re-appropriate the double register of being seen as cheaters or victim and react to it.